Financial Performance Analysis Using Liquidity, Solvency, Profitability and Activity Ratios at PT XL Axiata, Tbk - Johanes Wilfrid Pangihutan Purba; Yulita Santa Nova Girsang; Nursahrina Sinaga (Jurnal Ilmiah Accusi, 2026)
This study aims to measure and analyze the financial performance of PT XL Axiata Tbk for the 2019–2022 period using a financial ratio approach. This is a quantitative study that utilizes secondary data in the form of the company’s annual financial statements for the observation period. The analytical tools used include liquidity ratios (current ratio, quick ratio, and cash ratio), solvency ratios (debt-to-asset ratio and debt-to-equity ratio), and profitability ratios (Net Profit Margin, Return on Assets, and Return on Equity). The results indicate that, overall, the financial performance of PT XL Axiata Tbk during this period was suboptimal. The company’s liquidity ratios are classified as poor due to the low ability of current assets to cover current liabilities. Solvency ratios also indicate suboptimal conditions due to the high proportion of debt relative to equity. Furthermore, the company’s profitability ratios are classified as poor, reflecting the company’s insufficient efficiency in generating profits from the utilization of its total assets and equity